ANALISA BANGKITAN PERJALANAN PADA PERUMAHAN SEMPAJA LESTARI DIKOTA SAMARINDA - SORAIDA, EKHA (KURVA S JURNAL MAHASISWA, 2014)
The basic objective is to produce a lasting trip generation model of the relationship that links land use with the amount of motion in the A Zone. This stage aims to study and predict the level of trip generation by learning a few variations of the relationship between the characteristics of the environmental movement with the land use. Several studies have identified transportation correlation between the magnitude of the movement of the various variables, and each variable is also correlated with each other.